The Methuen drama guide to contemporary American playwrights - Middeke, Martin; Schnierer, Peter Paul; Homann, Greg (Bloomsbury Publishing, 2013)
The Methuen Drama Guide to Contemporary American Playwrights is an authoritative single-volume guide to the work of twenty-five American playwrights from the second half of the twentieth century, written by a team of twenty-five eminent scholars from the United States, Canada, Britain, Germany and Ireland contributing individual studies to the work of each playwright. Each of the twenty-five chapters provides: a biographical introduction to the playwright and their work; a survey and concise analysis of each of the writer's published plays; a discussion of their style, dramaturgical concerns a
Description based upon print version of record
Keywords: Electronic books